Reasons for poor academic achievement among public school students in the Qatraneh district in the Karak governorate (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed to uncover the causes of poor academic achievement of students in publicschools in the Qatraneh district in the Karak governorate, and the study sample consisted of (408) male andfemale students, and the study tool included (43) clauses distributed into three areas (student'sproblems,parent's problems, and school-specific problems).The results of the study showed that the general level ofstudents 'problems, according to the estimates of the study sample, came at a high or medium level, and thatthe general level of parents' problems came at a high level also for most of the clauses, also, the generallevel of school-specific problems came at an average level, and the results showed that there arestatistically significant differences for reasons of weakness and low academic and academic achievementamong public school students in the Qatraneh district in the Karak governorate for all fields of studyaccording to the gender variable.The study recommended the necessity of working to address the causes ofpoor academic achievement according to the fields of study.